Law and administrative aspects of water protection in Poland - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2011)
Water Law regulates water management in accordance with the principle of sustainable development, in particular the development and protection of water resources, water use, and water management. The legislature also clarified the matter of ownership of land and water and covered with water, and the principles of management of these components in relation to the assets of the Treasury. The statutory provisions indicate that water management is carried out in accordance with the principle of rational and comprehensive treatment of surface water resources and groundwater, including their quantity and quality and takes into account the principle of common interests and is accomplished through the cooperation of public administration, water users and representatives of local communities so to get the maximum benefit to society.